An investigation into the barriers to employment for unskilled workers in Site C, Khayelitsha and Du Noon, Milnerton : does spatial mismatch theory apply? - Goetz, Deborah Stacey (Department of Sociology, 2015)
Includes bibliographical references (leaves 53-56).